Supporting Head Start parents: impact of a text message intervention on parent–child activity engagement - Hurwitz, Lisa B.; Lauricella, Alexis R.; Hanson, Ann; Raden, Anthony; Wartella, Ellen (Early Child Development and Care, 2015)
Head Start emphasises parent engagement as a critical strategy in promoting children's long-term learning. Parents can support children's positive development by engaging them in stimulating activities. The following study assessed whether a service that delivered parenting tips via text message could prompt parents of children enrolled in Head Start programmes to engage in more learning activities with their children. Two hundred and fifty-six parents participated in the study with approximately half receiving text messages for six weeks. All participants completed a questionnaire about the types of learning activities in which they engaged their children. Parents who received the service engaged in more learning activities; this was particularly true of fathers and parents of boys. Parents reported high rates of satisfaction with service. These results suggest that text-based interventions as a supplement to other forms of family engagement may successfully communicate parenting information and support parental engagement with young children.
Keywords: Head Start; ___working_potential_duplicate; activities; early childhood; intervention; parenting; text messaging

Using Mobile Phone Texting to Support the Capacity of School Leaders in Ghana to Practise Leadership for Learning - Swaffield, Sue; Jull, Stephen; Ampah-Mensah, Alfred (Procedia - Social and Behavioral Sciences, 2013)
Several years into a collaborative professional development programme to build the Leadership for Learning capacity of Basic school headteachers throughout Ghana, the challenge is to sustain commitment, deepen understanding and share learning among the school leaders. Employing ubiquitous mobile phone technology, weekly text messages have been sent to the programme's 175 initial participants. During the year of the pilot project different forms of messages have been tried, and feedback from recipients suggests their value. The paper reports experience and findings from the pilot, and considers plans for scaling-up to reach all 18,000 Basic schools across the country.
Keywords: Ghana; Leadership for Learning; SMS; headteachers; mobile phone; professional development; school leaders; text messages

Sustaining and scaling pedagogic innovation in sub-Saharan Africa: Grounded insights for teacher professional development - Haßler, Björn; Hennessy, Sara; Hofmann, Riikka (Journal of Learning for Development, 2018)
Developing sustainable and scalable educational initiatives is a key challenge in low-income countries where donor-funded short-term projects are limited by both contextual factors and programme design. In this concept paper we examine some of the issues related to in-service teacher development in the context of sub-Saharan Africa, grounded predominantly in our experiences of over 5 years of iteratively developing, refining and evaluating an intensive school-based professional learning programme for primary school teachers. “OER4Schools” integrates interactive pedagogy, Open Educational Resources (OER) and use of mobile devices (where available). The focus of this paper is on identifying what the main factors are perceived to be in sustaining and scaling up such a programme, from the perspectives of participating teachers, workshop facilitators and the research team. Synthesising our previous research and drawing on recent work in the field, we identify the key characteristics of effective and sustainable professional learning in low-resourced contexts. Such characteristics include effective peer facilitation, school-based active learning, explicit programme structure, appropriate scheduling and resourcing, and mitigating resource constraints through use of OER. Our conclusions thereby offer insights concerning the importance and impact of wider influences on participation and engagement of stakeholders and lead to recommendations for programme design and implementation, that should be taken on board by future initiatives.
Keywords: AWP2; Active Learning; Africa; Author:Haßler; C:sub-Saharan Africa; CitedIn:DFID_SRF; CitedIn:OER4S-TPE-Anon; CitedIn:OER4Schools-2012-HHH1-anon; CitedIn:PhD_Thesis; DIAL-RDO; Developing Nations; Educational Technology; Elementary Secondary Education; Faculty Development; Foreign Countries; Handheld Devices; IMPORT_FROM_DFID_RITE; InPrep; Inservice Teacher Education; Low Income Groups; Motivation; OER4Schools; Open Educational Resources; Peer Teaching; RPF-May-2016; Resource Allocation; Rural Schools; Scaffolding (Teaching Technique); Scheduling; Shared Resources and Services; Sustainable Development; Sustainable Development Goal 4; Teacher Professional Development; Technology Uses in Education; Telecommunications; ___working_potential_duplicate; dode_eth-src-dode; dode_eth-trf2-dode; missingHU; peer-facilitation; school-based active learning; sub-Saharan Africa; ⛔ No DOI found

A tale of two communication tools: discussion-forum and mobile instant-messaging apps in collaborative learning - Sun, Zhong; Lin, Chin-Hsi; Wu, Minhua; Zhou, Jianshe; Luo, Liming (British Journal of Educational Technology, 2018)
Computer-supported collaborative learning (CSCL) has shown considerable promise, but thus far the literature has tended to focus on individual technological tools, without due regard for how the choice of one such tool over another impacts CSCL, either in outline or in detail. The present study, therefore, directly compared the learning-related uses of an online discussion forum against such use of a mobile instant-messaging app by the same group of 78 upper-division undergraduate pre-service teachers in China. The participants were asked to use one of the two communication tools during the first of three learning activities, then to switch to the other during the second, and to choose their preferred tool for the third. Based on the results of content analysis, social-network analysis and a survey of the students' attitudes, it was found that while both tools facilitated collaborative learning, they appeared to have different affordances. Specifically, using the online discussion forum resulted in more communication aimed at knowledge construction, while using the mobile instant-messaging app resulted in more social interactions.
Keywords: Applications programs; China; Collaborative learning; Collaborative virtual environments; Communication; Computer Mediated Communication; Computer Software; Computer assisted instruction--CAI; Content Analysis; Content analysis; Cooperative Learning; ERIC, Current Index to Journals in Education (CIJE); Education--Teaching Methods And Curriculum; Educational technology; Foreign Countries; Handheld Devices; Higher Education; Learning; Network Analysis; Network analysis; Preferences; Preservice Teachers; Social Networks; Social factors; Student Attitudes; Student Surveys; Synchronous Communication; Telecommunications; Tools; Undergraduate Students; __:import:01; __:match:final; __:matched; __:study_id:2096807; __finaldtb

A tale of two communication tools: discussion-forum and mobile instant-messaging apps in collaborative learning - Sun, Zhong; Lin, Chin-Hsi; Wu, Minhua; Zhou, Jianshe; Luo, Liming (British Journal of Educational Technology, 2018)
Computer-supported collaborative learning (CSCL) has shown considerable promise, but thus far the literature has tended to focus on individual technological tools, without due regard for how the choice of one such tool over another impacts CSCL, either in outline or in detail. The present study, therefore, directly compared the learning-related uses of an online discussion forum against such use of a mobile instant-messaging app by the same group of 78 upper-division undergraduate pre-service teachers in China. The participants were asked to use one of the two communication tools during the first of three learning activities, then to switch to the other during the second, and to choose their preferred tool for the third. Based on the results of content analysis, social-network analysis and a survey of the students' attitudes, it was found that while both tools facilitated collaborative learning, they appeared to have different affordances. Specifically, using the online discussion forum resulted in more communication aimed at knowledge construction, while using the mobile instant-messaging app resulted in more social interactions.
Keywords: Applications programs; China; Collaborative learning; Collaborative virtual environments; Communication; Computer Mediated Communication; Computer Software; Computer assisted instruction--CAI; Content Analysis; Content analysis; Cooperative Learning; ERIC, Current Index to Journals in Education (CIJE); Education--Teaching Methods And Curriculum; Educational technology; Foreign Countries; Handheld Devices; Higher Education; Learning; Network Analysis; Network analysis; Preferences; Preservice Teachers; Social Networks; Social factors; Student Attitudes; Student Surveys; Synchronous Communication; Telecommunications; Tools; Undergraduate Students; __:import:01; __:match:final; __:matched; __:study_id:2096807; __finaldtb

Improving educational outcomes & reducing absenteeism at remote villages with mobile technology and WhatsApp: findings from rural India - Nedungadi, Prema; Mulki, Karunya; Raman, Raghu (Education and Information Technologies, 2018)
Reduction of teacher and student absenteeism, together with consistent teacher support and training, are critical factors in improving the quality of education in rural India. As part of an ongoing project involving schools and educational centers in rural areas spread across 21 Indian states, this study investigated how implementation of two simple, accessible technologies could not only reduce absenteeism but also increase teachers' effectiveness and improve student performance. In addition to students and teachers, key stakeholders included educational coordinators who provided support and monitoring regarding use of WhatsApp and two additional apps designed specifically to support simple educational improvements. In our study we coded and analyzed nine months of messages (n = 8968), both photographs and texts, posted by 26 participants. The number of text messages related to attendance was strongly positively correlated with frequency of interactions between coordinators and teachers. Our approach resulted in increased teacher and student attendance, as well as improvements in lessons and other planned educational activities. This model functions well in rural settings where there is poor internet connectivity and lack of supporting infrastructure. Remote schools can easily adopt this tablet-based model to reduce teacher absenteeism, improve teaching techniques, improve educational resources, and increase student performance.
Keywords: Absenteeism; Academic Achievement; Attendance; Attendance Patterns; Computer Oriented Programs; Computers--Information Science And Information Theory; ERIC, Current Index to Journals in Education (CIJE); Educational Opportunities; Educational Quality; Educational technology; Foreign Countries; ICT; India; Monitoring; Quality of education; Rural Areas; Rural areas; Rural education; School education; Software; Students; Teacher Effectiveness; Teacher absence; Teacher monitoring; Teachers; Tele-education; WhatsApp; __:import:01; __:match:final; __:matched; __:study_id:2097863; __finaldtb

Improving educational outcomes & reducing absenteeism at remote villages with mobile technology and WhatsApp: findings from rural India - Nedungadi, Prema; Mulki, Karunya; Raman, Raghu (Education and Information Technologies, 2018)
Reduction of teacher and student absenteeism, together with consistent teacher support and training, are critical factors in improving the quality of education in rural India. As part of an ongoing project involving schools and educational centers in rural areas spread across 21 Indian states, this study investigated how implementation of two simple, accessible technologies could not only reduce absenteeism but also increase teachers' effectiveness and improve student performance. In addition to students and teachers, key stakeholders included educational coordinators who provided support and monitoring regarding use of WhatsApp and two additional apps designed specifically to support simple educational improvements. In our study we coded and analyzed nine months of messages (n = 8968), both photographs and texts, posted by 26 participants. The number of text messages related to attendance was strongly positively correlated with frequency of interactions between coordinators and teachers. Our approach resulted in increased teacher and student attendance, as well as improvements in lessons and other planned educational activities. This model functions well in rural settings where there is poor internet connectivity and lack of supporting infrastructure. Remote schools can easily adopt this tablet-based model to reduce teacher absenteeism, improve teaching techniques, improve educational resources, and increase student performance.
Keywords: Absenteeism; Academic Achievement; Attendance; Attendance Patterns; Computer Oriented Programs; Computers--Information Science And Information Theory; ERIC, Current Index to Journals in Education (CIJE); Educational Opportunities; Educational Quality; Educational technology; Foreign Countries; ICT; India; Monitoring; Quality of education; Rural Areas; Rural areas; Rural education; School education; Software; Students; Teacher Effectiveness; Teacher absence; Teacher monitoring; Teachers; Tele-education; WhatsApp; __:import:01; __:match:final; __:matched; __:study_id:2097863; __finaldtb

A tale of two communication tools: Discussion-forum and mobile instant-messaging apps in collaborative learning - Sun, Zhong; Lin, Chin-Hsi; Wu, Minhua; Zhou, Jianshe; Luo, Liming (British Journal of Educational Technology, 2017)
Computer-supported collaborative learning (CSCL) has shown considerable promise, but thus far the literature has tended to focus on individual technological tools, without due regard for how the choice of one such tool over another impacts CSCL, either in outline or in detail. The present study, therefore, directly compared the learning-related uses of an online discussion forum against such use of a mobile instant-messaging app by the same group of 78 upper-division undergraduate pre-service teachers in China. The participants were asked to use one of the two communication tools during the first of three learning activities, then to switch to the other during the second, and to choose their preferred tool for the third. Based on the results of content analysis, social-network analysis and a survey of the students' attitudes, it was found that while both tools facilitated collaborative learning, they appeared to have different affordances. Specifically, using the online discussion forum resulted in more communication aimed at knowledge construction, while using the mobile instant-messaging app resulted in more social interactions.

A tale of two communication tools: Discussion-forum and mobile instant-messaging apps in collaborative learning - Sun, Zhong; Lin, Chin-Hsi; Wu, Minhua; Zhou, Jianshe; Luo, Liming (British Journal of Educational Technology, 2017)
Computer-supported collaborative learning (CSCL) has shown considerable promise, but thus far the literature has tended to focus on individual technological tools, without due regard for how the choice of one such tool over another impacts CSCL, either in outline or in detail. The present study, therefore, directly compared the learning-related uses of an online discussion forum against such use of a mobile instant-messaging app by the same group of 78 upper-division undergraduate pre-service teachers in China. The participants were asked to use one of the two communication tools during the first of three learning activities, then to switch to the other during the second, and to choose their preferred tool for the third. Based on the results of content analysis, social-network analysis and a survey of the students' attitudes, it was found that while both tools facilitated collaborative learning, they appeared to have different affordances. Specifically, using the online discussion forum resulted in more communication aimed at knowledge construction, while using the mobile instant-messaging app resulted in more social interactions.

An Investigation of the Impact of an Intervention to Reduce Academic Procrastination Using Short Message Service (SMS) Technology - Davis, D; Abbitt, J (Journal of Interactive Online Learning, 2013)
This mixed-method pilot study investigated the impact of a custom Short Message Service (SMS) reminder system developed to help students reduce procrastination and increase performance on weekly content-related quizzes in a high-enrollment hybrid online course. Text message reminders were sent to three students with high procrastination and low performance levels on a schedule based on free-operant avoidance principles, where messages would be terminated upon completion of the weekly quiz. The results suggest that there was sufficient evidence that the system had a positive effect on procrastination levels, but less evidence for an effect on performance. Subsequent interviews with the participants confirmed the utility and potential of the system, and revealed areas for improvement in the implementation of the SMS reminder system as well as an understanding of the students’ response to the intervention.
Keywords: ⛔ No DOI found

Donor Organizations & the Principles for Digital Development: A Landscape Assessment and Gap Analysis. (Principles for Digital Development — Resource Development Program Asset No. 1) - Haßler, Björn; Brugha, Meaghan; Muyoya, Chisenga; Mitchell, Joel; Hollow, David; Jackson, Alan (Jigsaw and Open Develoment & Education, 2018)
Donor Organizations & the Principles for Digital Development: A Landscape Assessment and Gap Analysis. (Principles for Digital Development — Resource Development Program Asset No. 1)   Also available at https://digitalprinciples.org/resource/donor-organizations-the-principles-for-digital-development-a-landscape-assessment-and-gap-analysis/, https://digitalprinciples.org/wp-content/uploads/PDD2018_interactive.pdf
Keywords: _DOILIVE; _not_EdTechHub; _zenodoODE; dode_eth-src-dode; dode_eth-trf2-dode

Interaction in a discussion list: an exploration of cognitive, social, and teaching presence in teachers’ online collaborations - Nami, Fatemeh; Marandi, S Susan; Sotoudehnama, Elaheh (ReCALL: the Journal of EUROCALL, 2018)
Discussion lists have gained a significant popularity in professional development research over the past few decades for the opportunity they provide for asynchronous interaction. This article presents findings from a small-scale case study that aimed at exploring the nature of teachers’ asynchronous exchanges in a discussion list. The data comprised the archived log of the messages in a Yahoo Group discussion list by five in-service English as a foreign language (EFL) teachers who volunteered to take part in a hybrid computer-assisted language learning (CALL) teacher education course in a state university in Iran. The discussion list was incorporated into the course to engage participants in professional dialogue on topics related to technology/CALL. During the initial data analysis, participants’ asynchronous exchanges were grouped as suggestions, questions, unclassified, answers, and delivery, drawing upon Oriogun and Cave’s (2008) SQUAD categorization, following the constant comparative method of analysis. Through a follow-up computer-mediated discourse analysis, cognitive, social, and teaching presence functional moves were identified in the data. Participants used the space not only for socializing and peer instruction but also for constructing knowledge. Despite an uneven pattern of contribution, asynchronous exchanges provided opportunities for knowledge construction at different levels of cognitive presence on topics ranging from technology tools and their affordances/constraints to computer-assisted language testing, materials development, and classroom management. The findings provide CALL teacher education researchers and course designers insights into the potential of asynchronous interaction for online and blended language teacher education.
Keywords: Asynchronous Communication; Blended Learning; CALL teacher education; CASE studies; COMPUTER assisted language instruction; Cognitive processes; Collaborative learning; Colleges & universities; Computer Mediated Communication; Computer assisted instruction--CAI; Computer assisted language learning; Critical thinking; Curriculum development; Data analysis; Discourse Analysis; Distance learning; ERIC, Current Index to Journals in Education (CIJE); Educational Technology; Educational technology; English (Second Language); English as a second language instruction; Faculty Development; Foreign Countries; Foreign languages; Group Discussion; Higher Education; Higher education; Hybrid computers; Interactive learning; Iran; LANGUAGE & languages; Language Teachers; Linguistics--Computer Applications; PROFESSIONAL education; Professional development; School environment; Second Language Instruction; Second language teachers; Social factors; TEACHERS; Teacher Education Programs; Teacher education; Teachers; Teaching; Technology Uses in Education; __:import:01; __:match:final; __:matched; __:study_id:2095858; __finaldtb; asynchronous interaction; cognitive presence; online collaboration; social presence; teaching presence

The Effect of Teacher-Family Communication on Student Engagement: Evidence from a Randomized Field Experiment - Kraft, M; Dougherty, Shaun (Journal of Research on Educational Effectiveness, 2013)
In this study, we evaluate the efficacy of teacher communication with parents and students as a means of increasing student engagement. We estimate the causal effect of teacher communication by conducting a randomized field experiment in which sixth- and ninth-grade students were assigned to receive a daily phone call home and a text/written message during a mandatory summer school program. We find that frequent teacher–family communication immediately increased student engagement as measured by homework completion rates, on-task behavior, and class participation. On average, teacher–family communication increased the odds that students completed their homework by 40%, decreased instances in which teachers had to redirect students’ attention to the task at hand by 25%, and increased class participation rates by 15%. Drawing upon surveys and interviews with participating teachers and students, we identify three primary mechanisms through which communication likely affected engagement: stronger teacher–student relationships, expanded parental involvement, and increased student motivation.
Keywords: ___working_potential_duplicate

A Quasi-Experimental Study of the Classroom Practices of English Language Teachers and the English Language Proficiency of Students, in Primary and Secondary Schools in Bangladesh - Power, Tom; McCormick, Robert; Asbeek-Brusse, Elsbeth (2017)
English in Action (EIA) is an English language teacher development project based in Bangladesh that was intended to run from 2008 to 2017, but which was extended at the request of the Government of Bangladesh, with additional funding from UKAID, for a further year to 2018. By the time of the design of this study (2014-2015) EIA was drawing to the end of upscaling (phase III, 2011-2014) and entering institutionalisation and sustainability (phase IV, 2014-17, extended 2018). Successive prior studies had indicated substantial success in improving both teachers’ classroom practices and student learning outcomes, over the pre-project baseline (e.g. EIA 2011, 2012). The 2014 Annual Review of EIA recommended that in the final phase, EIA should explore whether it would be possible to carry out a study that compared a ‘counterfactual’ or control-group of teachers and students, to the ‘EIA’ or treatment schools: i.e. a Randomised Control Trial or Quasi-Experimental study. A proposal for a Quasi-Experimental study was developed in collaboration with DFID’s South Asia Research Hub (SARH), which also provided the additional funding necessary to implement such a study. The teachers and students who were the subject of this study, were the fourth cohort to participate in English in Action (together with teachers from ‘control’ schools, in the same Upazilas). This fourth EIA cohort included Schools, Teachers and Students from approximately 200 Upazilas (of approximately 500 in total) across Bangladesh, including some of the most disadvantaged areas (with reference to UNICEF deprivation index), such as Char, Hoar and Monga districts. Teachers took part in a school-based teacher development Programme, learning communicative language teaching approaches through carrying out new classroom activities, guided by teacher development videos that showed teachers, students and schools similar to those across the country. Teachers also had classroom audio resources for use with students. All digital materials were available offline, on teachers own mobile phones, so there is no dilution of the Programmes core messages about teaching and learning, by some intermediary coming between the teacher and the materials. Teachers were supported through these activities, by other teachers in their schools, by their head teachers and by local education officers. Some teachers from each area were also given additional support and guidance from divisional EIA staff, to act as Teacher Facilitators, helping teachers work through activities and share their experiences at local cluster meetings. Whereas previous cohorts of teachers had attended eight local teacher development meetings over their participation in the project, for Cohort Four, this was reduced to four meetings, with a greater emphasis being placed on support in school by head teachers, as well as support from local education officers. This change was part of the move towards institutionalisation and sustainability of project activities within and through government systems and local officers. The purpose of this study was both to provide the evaluation evidence required for the final phase of the EIA project and to contribute to the international body of research evidence on effective practices in teacher development in low-to-middle income country contexts.

Evaluation of the Transformative Potential of Positive Gender Socialization in Education for Peace Building. - Chinen, Marjorie; Elmeski, Mohammed (2016 Society for Research on Educational Effectiveness Conference, 2016)
American Institutes for Research (AIR) is conducting an impact evaluation of The United Nations Children's Emergency Fund's (UNICEF's) teacher-training program and reinforcing text messages that aim to provide meaningful knowledge regarding the transformative potential of positive gender socialization in education for peace building in the region of Karamoja, Uganda. The impact evaluation assesses the effects of the teacher-training program, with an emphasis on gender socialization, on teachers' knowledge, attitudes, and practices concerned with gender equity, and positive gender socialization. The authors implemented a mixed-methods research design for the impact evaluation, using quantitative and qualitative methods. They compared the outcomes of interest among the teachers who benefit from the program with the outcomes of interest of comparable teachers in different schools who do not benefit from the program. The impact evaluation is based on an eight-month intervention, with baseline data collected in March 2015 and endline data collected in November 2015. One hundred five schools from eight Coordinating Centre Tutors (CCTs) located in the districts of Abim, Kaabong, and Napak are participating in the study, with a third of the schools receiving the training plus reinforcing text messages (the "complete intervention" group), another third receiving the teacher training only (the "limited intervention" group), and the other third not receiving any of the interventions (the control or "business as usual" group). A total of 916 teachers working in the 105 schools at the time of baseline data collection were surveyed. Provided that the various stakeholders respond in the manner anticipated, the trainings--and potentially the active teacher support and engagement delivered using the mobile SMS platform--should lead to a set of initial effects or intermediate outcomes. Tables and figures are appended.
Keywords: Comparative Analysis; ERIC, Resources in Education (RIE); Educational Practices; Elementary Education; Elementary School Teachers; Foreign Countries; Inservice Teacher Education; Intervention; Mixed Methods Research; Outcome Measures; Peace; Program Effectiveness; Randomized Controlled Trials; Sex Fairness; Socialization; Synchronous Communication; Teacher Attitudes; Teacher Characteristics; Telecommunications; Uganda; __:import:01; __:match:final; __:matched; __:study_id:2097972; ___working_potential_duplicate; __finaldtb; ⛔ No DOI found

Evaluation of the transformative potential of positive gender socialization in education for peace building - Chinen, Marjorie; Elmeski, Mohammed (Society for Research on Educational Effectiveness, 2016)
American Institutes for Research (AIR) is conducting an impact evaluation of The United Nations Children's Emergency Fund's (UNICEF's) teacher-training program and reinforcing text messages that aim to provide meaningful knowledge regarding the transformative potential of positive gender socialization in education for peace building in the region of Karamoja, Uganda. The impact evaluation assesses the effects of the teacher-training program, with an emphasis on gender socialization, on teachers' knowledge, attitudes, and practices concerned with gender equity, and positive gender socialization. The authors implemented a mixed-methods research design for the impact evaluation, using quantitative and qualitative methods. They compared the outcomes of interest among the teachers who benefit from the program with the outcomes of interest of comparable teachers in different schools who do not benefit from the program. The impact evaluation is based on an eight-month intervention, with baseline data collected in March 2015 and endline data collected in November 2015. One hundred five schools from eight Coordinating Centre Tutors (CCTs) located in the districts of Abim, Kaabong, and Napak are participating in the study, with a third of the schools receiving the training plus reinforcing text messages (the "complete intervention" group), another third receiving the teacher training only (the "limited intervention" group), and the other third not receiving any of the interventions (the control or "business as usual" group). A total of 916 teachers working in the 105 schools at the time of baseline data collection were surveyed. Provided that the various stakeholders respond in the manner anticipated, the trainings--and potentially the active teacher support and engagement delivered using the mobile SMS platform--should lead to a set of initial effects or intermediate outcomes. Tables and figures are appended.
Keywords: Comparative Analysis; ERIC, Resources in Education (RIE); Educational Practices; Elementary Education; Elementary School Teachers; Foreign Countries; Inservice Teacher Education; Intervention; Mixed Methods Research; Outcome Measures; Peace; Program Effectiveness; Randomized Controlled Trials; Sex Fairness; Socialization; Synchronous Communication; Teacher Attitudes; Teacher Characteristics; Telecommunications; Uganda; __:import:01; __:match:final; __:matched; __:study_id:2097972; __finaldtb